2017
DOI: 10.1021/acs.energyfuels.7b01247
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Bioderived 1-Decanol to Diesel-like Fuel and Biobased Oil via Dehydration and Oligomerization Reactions

Abstract: The production of diesel-like fuel and base oil from bioderived fatty alcohol through a two-steps process, dehydration reaction and oligomerization reaction, was studied. The bioderived 1-decanol was converted to olefin mixtures and di-n-decyl ether via the dehydration over commercial γ-alumina catalysts with and without acid modification in a fixed-bed reactor at different temperatures. The catalysts studied were characterized using nitrogen adsorption, temperature-programmed desorption, X-ray diffraction, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…For any given reaction time (lower than 120 min), an increase in reaction temperature significantly enhanced the conversion of 1-decene. This result corresponded well with our previous investigation on the 1-decene oligomerization [4,5]. The higher the reaction temperature, the shorter the reaction time to reach the highest conversion of 1-decene.…”
Section: Effect Of Temperature On Oligomer Product Compositionsupporting
confidence: 92%
See 1 more Smart Citation
“…For any given reaction time (lower than 120 min), an increase in reaction temperature significantly enhanced the conversion of 1-decene. This result corresponded well with our previous investigation on the 1-decene oligomerization [4,5]. The higher the reaction temperature, the shorter the reaction time to reach the highest conversion of 1-decene.…”
Section: Effect Of Temperature On Oligomer Product Compositionsupporting
confidence: 92%
“…In Lewis acid catalysis, oligomerization is activated by a hydrogen donor agent such as water, called cationic oligomerization [3]. Other agents for oligomerization include heterogeneous acid catalysts such as sulfatedalumina [1], tungsten-zirconia [4] and zeolite [5] that are cheaper than other types of catalysts. One important feature of zeolite catalysts is that their inner structure can be manipulated to tailor products [6,7], while spent zeolite catalysts can be simply regenerated via chemical or thermal treatment [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, lower α-olefin oligomers obtained by cationic oligomerization were exceedingly defined as structurally uniform reaction products [16,17]. Moreover, most of the recent publications devoted to the oligomerization of higher α-olefins have discussed acid-catalyzed processes [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…(11), productivity can be predicted by plugging in the operating time of the distillation unit. Comparison between experimental data and productivity calculated by the polynomial equation produced R 2 very close to 1 which suggested that these predictions were accurate [21,22]. Productivity=4x10 -7 to 6 -3x10 -5 to 5 +0.0008to 4 -0.0096to 3 + 0 .…”
Section: Distillation Rate and Productivity Of The Distillation Unitmentioning
confidence: 67%